The Performance, Nutrient Digestibility, Aflatoxin B1 Residue, and Histopathological Changes of Broilers Exposed to Dietary Mycosorb - C. L. Nalle; M. A. J. Supit; A. H. Angi; N. S. Yuliani (Tropical Animal Science Journal, 2021)
Aflatoxin B1 (AFB1) is the most dangerous type of aflatoxin that can impair poultry productivity even in low concentrations. The harmful effects of AFB1 should be minimized. The present study was conducted to evaluate the performance, nutrient digestibility, AFB1 residue, and histopathological changes of broilers fed AFB1 diets supplemented with mycosorb. Two hundred-forty 1-day old broiler chicks were allocated randomly to 24 pens (10 birds/pen). The experimental design was a 4 x 2 factorial arrangement, with AFB1 level and yeast glucomannan (mycosorb) supplementation as the main factors. The treatment diets were control diet; control diet + mycosorb; AFB1 diets (10.36 ppb); AFB1 diets (10.36 ppb) + mycosorb; AFB1 diets (26.97 ppb); AFB1 diets (26.97 ppb) + mycosorb; AFB1 diets (61.06 ppb); AFB1 diets (61.06 ppb) + mycosorb. The results showed that there was no interaction effect was found between the level of AFB1 and mycosorb on the performance and nutrient digestibility. The level of AFB1 did not affect dry matter digestibility coefficient but affected (p<0.05) crude fat digestibility coefficient of broilers. Except for proventriculus, level of AFB1 did not affect bird’s gut size. AFB1 residue was not detected in the broiler tissues fed all diets. Mycosorb alone ameliorated (p<0.05) feed conversion ratio (FCR) of growing birds. The birds fed 61.06 ppb AFB1 diets had darker liver than those fed similar diets added with mycosorb. The addition of mycosorb in AFB1 diets did not heal the hemorrhagic intestines of the birds. In conclusion, feeding low level of AFB1 diets added with mycosorb did not improve the bird’s performance, nutrient digestibility, or gut health. Mycosorb alone improved feed efficiency of the experimental birds.